Oxidative Stress Promotes Asexual Reproduction and Apogamy in the Red Seaweed Pyropia yezoensis - Takahashi, Megumu; Mikami, Koji (Frontiers in Plant Science, 2017)
The marine red seaweed Pyropia yezoensis has a haploid-diploid life cycle wherein two heteromorphic generations, a haploid gametophyte and a diploid sporophyte, are reciprocally generated from conchospores and carpospores, respectively. When we treated gametophytic blades of P. yezoensis with H2O2, discharge of asexual monospores was accelerated, resulting in increased numbers of gametophytic clones. Production of sporophytes without fertilization of male and female gametes was also observed. These findings indicate that oxidative stress can induce vegetative cells to develop into monospores that produce gametophytes asexually and can sometimes prompt carpospores to develop into sporophytes. The discovery of oxidative stress-triggered asexual reproduction and -apogamy will stimulate progress in studies of life-cycle regulation in P. yezoensis.